(untitled) (De Musica, 2024)
In this paper, I reflect on nonlinearity in some musical compositions and improvisations. The nonlinear analyses written by Jonathan Kramer are well known. I intend to extend a similar approach to musical compositions, improvisations and performances by adopting the perspective of the musician who restores the relationship between linearity and nonlinearity in the concrete act of musical performance.